Safety of bronchoscopic guided percutaneous dilatational tracheostomy in ICU patients in Tabriz City - Hejazi, Mohammad Esmaeil; Rezazadehsaatlou, Mohammadamin; Namvar, Leila; Sadeghi, Armin; Hejazi, Veghar; Hejazi, Yasin; Aghazadeh, Katrin Buyuk (Faculty of Medicine, Trisakti University, 2017)
BACKGROUNDTracheostomy is one of the most frequently performed procedures in intensive care units. The widespread attraction of percutaneous dilatational tracheostomy (PDT) is increasing in modern intensive care units (ICU). Bronchoscopic guidance seems to secure the safety of the technique. Multiple studies done to explain characterize differences in complications and cost-effectiveness of open and percutaneous tracheotomy. The objective of this study was to evaluate the benefits of percutaneous dilatational tracheostomy (PDT) using the Ciaglia technique with bronchoscopic guidance.METHODSA total of 100 elective percutaneous dilatational tracheostomies using the Ciaglia technique with a little modification were performed under flexible fiber optic bronchoscopic guide. The demographic variables were recorded, the underlying cause for patientâ€™s referred to the center for PDT, and intraoperative as well as early postoperative complications. Patients followed for several days after tracheostomy for early complications.RESULTSNo severe complications related to percutaneous dilatational tracheostomy were noticed during and after the procedure. Three patients had bleeding during incision and two led to subcutaneus hematoma. There were no other complications such as infection, emphysema and puncture ofÂ posterior wall.CONCLUSIONSWe recommended the use of endoscopic guidance bedside percutaneous tracheostomy using the Ciaglia technique with a little modification because it is safe and simple to do without significant complications. PDT with bronchoscopic guidance is a safe and easy procedure that can be done at the bedside setting.